Síntese e avaliação das atividades antiproliferativa e antimicrobiana de derivados 1-fenilssubstituído β-carbolínicos contendo as unidades 1,3,4-oxadiazol -2-ona e 1,3-oxazol-5-ona na posição-3 - Savariz, Franciele Cristina (2013)
Several research has been developed on the synthesis of β-carboline derivatives with different substituents, mainly at positions-1 and -3 of the β- carboline ring, aiming the preparation of compounds with biological activities, among them, antitumor and antimicrobial activities. Studies previously carried out by our research group showed that β-carbolines with substituted phenyl groups at position-1, and different heterocyclic at position-3, presented potent antiprotozoal, antiviral, antitumor and antimicrobial activities. Compounds containing the 1,3,4-oxadiazol-2-one and 1,3-oxazol-5-one units are reported in literature for possessing diverse important pharmacologic activities. The potentiality of these nuclei, associated to that presented for the β-carbolines, motivated us to the development of the present work, expecting to obtain new antitumor and antimicrobial agents. In the first part of this work we describe the synthesis, antitumor and antimicrobial activities of the new compounds 1-substitutedphenyl 3-(2-oxo-1,3,4-oxadiazol-5-yl)-β-carbolines (87a-g) and of its bases of Mannich, 1-substituted phenyl 3-[2-oxo-3-(alkylaminomethyl)-1,3,4-oxadiazol-5-yl]-β- carbolines (88-92 ad). The β-carboline-3-carbohydrazides (86a-g), intermediate for the synthetic route for the preparation of the desired derivatives were prepared by the Pictet-Spengler condensation, under acid catalyses, of L-tryptophan methyl ester (83) with aromatic aldehydes containing electron donating and withdrawing groups, followed of oxidation with sulphur of 3-carbomethoxy-tetrahydro-β- carbolines (84a-g), and further treatment with hydrazine hydrate. For the preparation of the derivatives 1-substitutedphenyl 3-(2-oxo-1,3,4-oxadiazol-5-yl)-β-carbolines (87a-g) the β-carboline-3-carbohydrazides (86a-g) were submitted to the reaction with 1,1 -carbonyldiimidazole, in DMF, afforded the products in 20 - 80% yield. The derivatives 87a-d were then submitted to the condensation with different amines, in presence of formaldehyde, to give the respective Mannich bases, 3-[2-oxo-3-(alkyllaminomethyl)-1,3,4-oxadiazol-5-yl]-β-carbolines (88 - 92 a-d) in 20 to 70% yield. The second part of this work involved the synthesis, antitumor and antimicrobial activities of the new β-carbolines with the 4-(substituted-benzylidene)-1,3-oxazol-5-one unit in the position-3. For the preparation of desired 1,3-oxazolones, the 3-carbomethoxy-β- carbolines (85) was used as starting material, which was subjected to hydrolysis with sodium hydroxyde, in water/methanol, to afford the 3-carboxy-β-carbolines (142). From the reaction of 142 with glycine hydrochloride ethyl ester, followed for hydrolysis of the terminal ester, and Plöchl-Erlenmeyer reaction with different aldehydes, in anhydride acetic/sodium acetate, led to the 1-substituted phenyl-3-(substituted benzylidene)-5-oxo-1,3-oxazol]-β-carbolines (146-149), with 30 - 42% yield. All novel compounds were characterized by their data HR-ESIMS, IR, 1H and 13C NMR and HSQC. The synthesized compounds were evaluated against a panel of human tumor cell lines, and towards different microorganisms, including bacteria and fungi. Among the evaluated compounds, the derivatives 1-(p-dimethylaminophenyl)-3-(2-oxo-1,3,4-oxadiazol-5-yl)-β-carboline (87b), 1-phenyl-3-[3-(morpholylmethyl)-2-oxo-1,3,4-oxadiazol-5-il)-β-carboline (92b) and 1-(p-methoxyphenyl)-3-(4-benzylidene-5-oxo-1,3-oxazol-2-yl)-β-carboline (149) showed GI50 values less than 10 μM, being potential candidate for in vivo studies. The antimicrobial assay results showed that all synthesized compounds were inactive, presenting GI50 > 100 μM. In order to select candidates for in vivo assays, an in silico study of the ADME (absorption, distribution, metabolism and excretion) properties of the novel synthesized β-carboline derivatives was carried out by investigating their Lipinski s parameters, topological polar surface area (TPSA) and percentage of absorption (% ABS).